Pleasure-suffering indicators of nursing work in a hemodialysis nursing service - Francine Cassol Prestes; Carmem Lúcia Colomé Beck; Tânia Solange Bosi de Souza Magnago; Rosângela Marion da Silva (SciELO, 2015)
OBJECTIVE To measure the pleasure and suffering indicators at work and relate them to the socio-demographic and employment characteristics of the nursing staff in a hemodialysis center in southern Brazil. METHOD Quantitative research, with 46 workers. We used a self-completed form with demographic and labor data and the Pleasure and Suffering Indicators at Work Scale (PSIWS). We conducted a bivariate and correlation descriptive analysis with significance levels of 5% using the Epi-Info® and PredictiveAnalytics Software programs. RESULTS Freedom of Speech was considered critical; other factors were evaluated as satisfactory. The results revealed a possible association between sociodemographic characteristics and work, and pleasure and suffering indicators. There was a correlation between the factors evaluated. CONCLUSION Despite the satisfactory evaluation, suffering is present in the studied context, expressed mainly by a lack of Freedom of Speech, with the need for interventions to prevent injury to the health of workers.